Tell no one eaudiobook - Coben, Harlan (Recorded Books Inc., 2012)
Critically acclaimed, bestselling author Harlan Coben has won the Shamus, Anthony, and Edgar awards during his impressive career. Tell No One is an irresistibly suspenseful thriller infused with nail-biting tension and packed with shocking plot twists. It has been eight years since Dr. David Beck's wife, Elizabeth, was murdered by a serial killer. When Beck receives a message containing a phrase only Elizabeth should know, he is tormented to tears. Either someone is playing a sick joke, or the wife he's never stopped loving is still alive. He's been warned to tell no one, and as the desperation of his search for the truth intensifies, he heads straight toward a deadly secret. This audiobook includes an exclusive interview with the author.